How Does Optimize Peer to Peer Lending Investment - Wahyu Mulyadi; Budi Purwanto; Nurhidayah Kusumaningrum Fadhilah (UniSadhuGuna Business School, 2024)
This research uses general data about loans in 5 Credit Grades A, B, C, D and E which can be obtained from the KoinWorks P2PL factsheet platform. The research results show that there are 4 combinations of funding assets in the calculation of the optimal portfolio of the Markowitz Model with the lowest risk preferences consisting of funding assets in Credit Grades A, B, D and E with an expected portfolio return of 24.29% for the year and 2.02. % for monthly and the best risk level in a year of 1.39% for annual and 0.11% for monthly. Meanwhile, in the optimal portfolio planning of the Markowitz model with sharpe ratio, there are 3 combinations of funding assets consisting of Credit Grades A, B and D which obtain an expected portfolio return of 18.29% in the current year and 1.52% in that month. and the level of risk. best in a year of 1.39% for this year and 0.48% for this month, and portfolio performance of 13.1.